President's Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2020)
Although you will be reading this President’s message in the June issue of the ORNAC Journal it was written ahead of time in the early days of the COVID-19 pandemic. As COVID-19 continued to spread my thoughts were, and still are, with all of you during this challenging time that we face together as a profession and as a country.